Bronchoscopic concerns in Proteus syndrome: a case report - Jung-Min Hong; Hyeon Jeong Lee; Eun Soo Kim; Hae-Kyu Kim; Soeun Jeon; Hyae-Jin Kim (Korean Journal of Anesthesiology, 2016)
Proteus syndrome (PS) is a rare congenital hamartomatous disorder with multisystem involvement. PS shows highly clinical variability due to overgrowth of the affected areas, and several features can make anesthetic management challenging. Little is known about the airway problem associated with anesthesia in PS patients. An 11-year-old girl with PS was scheduled for ear surgery under general anesthesia. She had features complicating intubation including facial asymmetry and disproportion, abnormal teeth, limitation of neck movement due to torticollis, and thoracolumbar scoliosis. This study reports on a case of deformed airway of a PS patient under fiberoptic bronchoscopy.